Taboo obsessions and their association with suicidality in obsessive-compulsive disorder - Cervin, Matti; do Rosário, Maria Conceição; Fontenelle, Leonardo F.; Ferrão, Ygor A.; Batistuzzo, Marcelo C.; Torres, Albina R. [UNESP]; Damiano, Rodolfo F.; Fernández de la Cruz, Lorena; Miguel, Euripedes C.; Mataix-Cols, David (Elsevier, 2022)
Individuals with obsessive-compulsive disorder (OCD) more often think about, attempt, and die by suicide than individuals from the general population. Sexual and religious obsessions (i.e., taboo obsessions) have been linked to increased risk of suicidality, but it is unclear if they explain additional risk over and above other risk factors. We refined the recently proposed multidimensional hierarchical model of OCD and explored how each symptom dimension in the model was associated with suicidality in a random half (n = 500) of a well-characterized cohort of patients with OCD. Symptom dimensions and other risk factors significantly associated with suicidality were included in a confirmatory multivariable model conducted with the other half of the sample (n = 501). The predictive confirmatory model accounted for 19% of the variance in suicidality. Taboo obsessions, the general OCD factor (i.e., having many different OCD symptoms at the same time), lifetime major depression, and lifetime substance use disorders significantly predicted suicidality in this model. Lifetime major depression explained most unique variance in suicidality (5.6%) followed by taboo obsessions and the general OCD factor (1.9% each). Taboo obsessions explain a small but significant proportion of variance in suicidality and should be considered an independent risk factor for suicidality in patients with OCD.
Keywords: Comorbidity; Heterogeneity; obsessive-Compulsive disorder; Suicidality; Symptom dimensions